2002
DOI: 10.1152/japplphysiol.01144.2001
|View full text |Cite
|
Sign up to set email alerts
|

Earliest cardiac toxicity induced by iron overload selectively inhibits electrical conduction

Abstract: Earliest cardiac toxicity induced by iron overload selectively inhibits electrical conduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 31 publications
2
37
0
Order By: Relevance
“…The effects of iron overload on mortality are consistent with observations showing that free radical-mediated lipid peroxidation alters cardiomyocyte electrophysiology 42,50 and Ca 2ϩ handling 20,43 and blockade of electrical conduction and sudden death in iron-overloaded guinea pigs. 51 Our strategy was to increase myocardial taurine levels to protect the cardiovascular system and prevent iron overloadinduced cardiovascular dysfunction, even though myocardial taurine levels were not affected by iron overload. This rationale is based on the observation that in the setting of increased oxidative stress, there appears to be an increased (conditioned) demand for taurine.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of iron overload on mortality are consistent with observations showing that free radical-mediated lipid peroxidation alters cardiomyocyte electrophysiology 42,50 and Ca 2ϩ handling 20,43 and blockade of electrical conduction and sudden death in iron-overloaded guinea pigs. 51 Our strategy was to increase myocardial taurine levels to protect the cardiovascular system and prevent iron overloadinduced cardiovascular dysfunction, even though myocardial taurine levels were not affected by iron overload. This rationale is based on the observation that in the setting of increased oxidative stress, there appears to be an increased (conditioned) demand for taurine.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar way, increased QTc dispersion may also be an indicator of higher risk for arrhythmia and sudden death in thalassaemia major patients. In vitro and in vivo studies have shown that a myocardial iron might change electrical conduction of the cardiomyocytes and lead to sudden death in the patients with iron overload [21,22]. The mechanism of arrhythmia induced by iron accumulation might be due to the loss of functional Na + channels and enhance Na channel inactivation, resulting in a reduced overshoot of cardiac action potential.…”
Section: Discussionmentioning
confidence: 99%
“…MR-T2* seems to be superlative (but costly) in terms of noninvasiveness, earliness (sensitivity) and accuracy (specificity), due to its ability to simultaneously assess both cardiac iron and structure, as well as cardiac function. Although cardiac dysfunction is more clinically obvious than conduction disturbance or arrhythmias in iron-overloaded patients, the pathogenesis of arrhythmias may start at the same time, with, or even earlier, than contractile dysfunction (39). It has been shown that when patients have symptoms of arrhythmias, the mortality rate is potentially high (12).…”
Section: Assessment For the Development Of Iron Overload Cardiomyopathymentioning
confidence: 99%
“…In ex vivo guinea pig hearts, delayed and blocked electrical conduction has been demonstrated to occur earlier in iron-loaded cardiac toxicity than impaired contractility (39). An optical mapping study of ironloaded Mongolian gerbils (77) also exhibited pertinent results of slow conduction and impulse block, with evidence of re-entry, which may lead to cardiac arrhythmias.…”
Section: Mechanisms Of Electrical Disturbance In Iron Overload Cardiomentioning
confidence: 99%